Basmati rice– Do not allow to lodge your crop - Singh, J P; Singh, Prem; Singh, Devendra (Indian Farming, 2015)
Farmers of northern states of the country should prefer to grow variety Basmati ‘Tarawari’ in place of existing diseases and pests susceptible and low yielding varieties. The problem of lodging in ‘Tarawari’ in particular and others in general can be minimized by the use of balanced fertilization in both the crops of the system (ricewheat) instead of cutting rice plant above primordial portion. Substitution with one fourth of nitrogen by FYM not only increased productivity and profitability of the system but also improved soil fertility.